Anti-Glycemic and Anti-Hepatotoxic Effects of Mangosteen Vinegar Rind from Garcinia mangostana Against HFD/STZ-Induced Type II Diabetes in Mice - Karim Naymul; Jeenduang Nutjaree; Tangpong Jitbanjong (Polish Journal of Food and Nutrition Sciences)
This study focuses on anti-glycemic and anti-hepatotoxic effects of mangosteen vinegar rind (MVR) on five weeks high-fat diet (HFD) / single dose streptozotocin (STZ) 30 mg/kg BW induced male ICR diabetic mice. Mice were randomly divided into five groups (n=6), normal control, diabetic control, and diabetic groups treated with MVR 100, 200 mg/kg BW and glibenclamide 60 mg/kg BW for one week. After the treatment, lipid profile, glycogen and bilirubin contents, oxidative damage (malondialdehyde, MDA), aspartate aminotransferase (AST) and alanine aminotransferase (ALT) activities, antioxidant enzymes: superoxide dismutase (SOD), catalase (CAT) were measured in plasma and/or liver tissues. MVR and glibenclamide treatment to HFD/STZ-induced diabetic mice significantly reduced their plasma glucose, plasma lipid profile, and hepatic lipid profile (P<0.05). Increased hepatic glycogen content indicates improvement of insulin sensitivity. Moreover, oxidative damage markers were ameliorated in MVR- and glibenclamide-treated groups compared to the diabetic control group. MVR with phenolic compounds content of 75 mg GAE/g dry weight and antioxidant potential of 303 mmol/L Trolox/g dry weight acted as a hepatoprotective agent against oxidative damage.